UJI AKTIVITAS ANTIDIABETES KOMBINASI EKSTRAK ETANOL DAUN ECENG GONDOK (Eichhornia crassipes (Mart.)Solms) DAN DAUN SINTRONG (Crassocephalum crepidioides (Benth.) S. Moore) PADA MENCIT - Andri Priyoherianto; Panji Ratih Suci; Putri Rizki Cahya Fatimah; Atik Nur Wijayanti (Jurnal Insan Farmasi Indonesia, 2021)
Diabetes mellitus is a chronic metabolic disorder that occurs due to destruction of pancreatic ? cells characterized by blood glucose levels that exceed normal limits. The purpose of this study was to determine the therapeutic effect of the combination of water hyacinth leaf extract and Sintrong leaf in reducing blood glucose levels in alloxan-induced experimental animals. Water hyacinth leaf powder and Sintrong leaves were extracted using the maceration method with 70% ethanol as a solvent. A total of 25 mice were divided into 5 groups, namely negative control CMC-Na 0.5%, positive control glibenclamide 0.00065 mg / g BW, water hyacinth leaf extract 17.5 mg / kg BW, Sintrong leaf extract 10.5 mg/ kg BW and a combination of water hyacinth leaf extract 17.5 mg / kg BW and sintrong leaf 10.5 mg / kg BW. The results showed that a single extract of water hyacinth and Sintrong leaves was able to reduce blood sugar levels for 7 days. The combination dose was effective in reducing blood sugar levels with a combination dose of 17.5 mg/ kg water hyacinth leaf extract in combination for 7 days.